PELAKSANAAN DERADIKALISASI NARAPIDANA TERORISME DI LEMBAGA PEMASYARAKATAN KELAS I CIPINANG - Farid Septian (Jurnal Kriminologi Indonesia, 2011)
Penitentiary, on one side is a vulnerable place for inmates’ deradicalization. On the other side, it plays an important role as positive transformation incubator for the inmates. It is truly depends on inmates’ coaching model, especially terorism inmates’ coaching. Radicalization here, is a flourishing and spreading process of radical values brought by terorism inmates to the others. This research has done in Cipinang class I penitentiary, using qualitative methods. The goal of this research is to know the terorism inmates’ coaching pattern in order to deradicalize them and what kind of problems that occurs during the process. In implementation of terorism inmates’ deradicalization, Cipinang class I penitentiary is cooperates with MUI, Depag and NGO. There are obstacles, which are inadequate facilities and infrastructure, “hard” character of the terorism inmates, coaching staff’s condition which still needs for quality and quantity upgrades, and lack of goverment and society’s support.